Changes in biochemical signs and electrolyte concentration in acute myocardial infarction - A. A. Ali; A. K. A. Hussein; R. M. Khalaf; A. A. Sahib (Regulatory Mechanisms in Biosystems, 2025)
Acute myocardial infarction (AMI) remains a leading cause of morbidity and mortality worldwide. Electrolyte imbalances, particularly alterations in sodium, potassium, calcium, magnesium, and chloride, play a significant role in cardiac electrophy siology and may influence the clinical course of AMI. To assess the prevalence and patterns of electrolyte disturbances in patients with AMI and to evaluate their association with comorbid hypertension and diabetes mellitus , a case–control study was co n ducted at the Heart Hospital in Nasiriyah, Southern Iraq, between October 2021 and March 2022. The study enrolled 100 partic i pants, including 51 patients with recent-onset AMI and 49 healthy controls. AMI diagnosis was confirmed according to ESC, ACC, AHA, and WHF guidelines. After an overnight fast, venous blood samples were collected and analyzed for serum sodium, potassium, chloride, calcium, and magnesium using a COBAS C411 analyzer, with verification by spectrophotometry. Among AMI patients (n = 51), hyponatremia was detected in 14 cases (27.5%), hypokalemia in 12 cases (23.5%), and hypocalcemia in 25 cases (49.0%). Electrolyte disturbances were more frequent among patients with hypertension (n = 46) and diabetes mellitus (n = 31) compared with those without these comorbidities. Potassium imbalance emerged as the most significant alteration, present in nearly two-thirds of the cases. Deficiencies in calcium and magnesium showed a strong association with sodium–potassium imbalance. Electrolyte disturbances, particularly hyponatremia and hypokalemia, are common in AMI and may co n tribute to adverse clinical outcomes. Early detection and correction of these abnormalities are essential for improving prognosis in AMI patients.